Serum Concentration of Vitamin D in Patients with Oral Lichen Planus - Ana Družijanić; Livia Cigić; Ana Glavina; Mirna Draganja; Dinko Martinović; Mare Ković (University of Zagreb. School of Dental Medicine, 2023)
Objectives: The vitamin D receptor is involved in immunologically mediated diseases such as oral lichen planus. Some studies suggest an association between lower vitamin D concentrations and a higher risk of inflammatory conditions such as oral lichen planus. The aim of this study was to investigate 1) whether there is a difference in serum vitamin D concentration in patients with oral lichen planus compared to patients in the control group, 2) whether there is a difference in serum vitamin D concentration in patients with erosive compared to non-erosive forms of oral lichen planus, 3) whether there is a difference in serum vitamin D concentration in patients with developed oral cancer and those without cancer. Material and Methods: The study included 68 patients, 34 with oral lichen planus and 34 healthy controls. Fasting venous blood was taken from each participant to determine serum concentrations of vitamin D. Results: The T-test results confirmed a statistically significant lower serum vitamin D concentration in patients with oral lichen planus compared to the control group (p=0.001). According to the results, a statistically significant lower serum vitamin D concentration was found in patients with erosive form OLP. All five patients with oral cancer, which was developed from erosive OLP, had low serum vitamin D concentrations. Conclusions: Determination of serum vitamin D concentration could be important for monitoring OLP patients to prevent the development of severe clinical manifestations of erosive OLP and the conversion of symptomatic lesions to oral cancer.